Understanding the influence of simulated elderly gastrointestinal conditions on nutrient digestibility and functional properties. (November 2022) - Makran, Mussa; Miedes, Diego; Cilla, Antonio; Barberá, Reyes; Garcia-Llatas, Guadalupe; Alegría, Amparo
Abstract: Background: The increase in the senior population has enhanced the interest in evaluating the food digestibility in that age group, using simulated digestion methods. Scope and approach: The effects of gastrointestinal changes on food digestion in the elderly were reviewed. Articles with an elderly-adapted simulated gastrointestinal digestion were selected (28 of 136 screened). Key findings and conclusions: The changes in oral physiology affect food disintegration, with consequences in perception and food digestion. Under elderly conditions ( vs. adult), proteolysis tends to be diminished or delayed, but the lack of harmonization of methodology does not allow conclusive results to be drawn. An increase in lipid digestibility was observed, although the contribution of gastric lipase remains unknown. A lower lactose release and changes in starch hydrolysis dependent on the food matrix and system model (static or dynamic) were related. Oral phase adaptation and the inclusion of non-glycolytic enzymes should be considered in future studies. The micronutrient bioaccessibility (Ca, vitamins A, D and E) was reduced under elderly conditions. These conditions may modify the bioactivity of digesta release (enzymatic inhibitory properties and, antioxidant capacity), depending on the bioactive compound. Besides, there are scarce studies carried out on the bioaccessibility of bioactive compounds (capsaicin, plant sterols, polyphenols). All these findings could shed additional light on the development of foods adapted to the requirements of older people, reducing the incidence of malnutrition, and be useful in the design of dietary recommendations in this population group, although they need to be confirmed by further in vivo studies. Highlights: In vitro digestions allow the evaluation of the age-related digestibility changes. Proteolysis is widely studied, but there are few studies evaluating micronutrients. Carbohydrate and protein digestibility are reduced, with an increase in lipolysis. Bioaccessibility of calcium and vitamins are reduced in elderly conditions.